Manifold Molecular Signaling Targets of Tropolones in Multifarious Diseases (Asian Journal of Pharmaceutics (AJP), 2021)
Tropolones are strewed phytochemicals having scaffold contains seven-membered ring system belongs toa family of Cupressaceae plants. Tropolone derivatives targeting multiple signaling transcription factors, cellcycle regulatory components, proteins, growth factors, kinases, and cytokines also involved in inflammatorymechanisms as well as involved in antioxidant, antimicrobial, anti-inflammatory, antithrombotic, and anticanceractivities. To identify the therapeutically potent pharmacophores from the natural components is the long-termfocus in pharmaceutical industry. Our preliminary findings on Hinokitiol (HIOL) showed binding potential inmitogen-activated protein kinase and ABL proto-oncogene 1 by in silico docking method perhaps in apoptosisof several cancers. This review aimed at gathering most of the available information to document the potentialefficacy of tropolones and its molecular mechanisms. Although natural products usually have fewer activitiescompared with synthesized compounds, it will shed a light on studies aiming to discover new drugs from tropolonederivatives for targeting multiple signaling mechanisms for various diseases.